Vanishing bile duct syndrome in pediatric population: An updated case-based review - H. C. Gopika Nair, Shilpa Rachel Thomas, S. I. Prithika, P. Ajay Samraj, K. Sumathi, Keerthana Chandrasekar (Journal of Applied Pharmaceutical Science, 2021)
Vanishing bile duct syndrome (VBDS) is a rare and rapidly progressing condition where there is massive destruction or loss of the bile duct. The etiology of VBDS includes developmental abnormalities, immune-mediated, infectious disorders, drug-induced, neoplastic, and ischemic disorders. Certain drugs that are responsible for the development of this disease are non-steroidal anti-inflammatory drugs, sex steroids, antidepressants, immunomodulators, and antibiotics. The exact mechanism behind the progression of this condition is not established. The clinical presentation ranges from the presence of dark urine, discolored stools, pruritus, maculopapular rashes, jaundice, and liver failure in extreme cases. A confirmatory test for the diagnosis of VBDS is the presence of ductopenia, which is a 50% reduction of the interlobular bile duct in liver biopsy. Currently, treatment is to remove the offending agent and provide supportive care with drugs like Ursodeoxycholic acid, corticosteroids, and immunosuppressants. Prognosis varies from hepatic failure to liver transplantation and it may also result in death. This case-based review briefs the seven documented pediatric cases of acute drug-related VBDS. Based on these articles, different treatment options were analyzed to provide a better prognosis for patients who are suffering from VBDS.
Keywords: Vanishing bile duct syndrome, etiology, pharmacological treatment, quality of life